Pengaruh Profitabilitas, Pajak, Mekanisme Bonus, Kepemilikan Asing, Debt Covenant Dan Intangible Assets Terhadap Transfer Pricing (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Tahun 2015 – 2017) - Destriana Br Ginting; Yulita Triadiarti; Erny Luxy Purba (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2019)
Abstrak :  The problem in this research is Transfer pricing is a company policy in determining the price of transactions between division members in a multinational company, which makes it easy for companies to adjust internal prices for goods, services and intangible assets traded so as not to create prices that are too low or too high. But in practice transfer pricing is one of the efforts of corporate tax planning with the aim of minimizing the tax burden that must be paid by engineering transfer prices between companies that have special relationships. The population of this research is 143 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The research sample was 16 companies with purposive sampling method, with quantitative research types. The data used is secondary data, namely the company's financial statements obtained from www.idx.co.id. The data analysis technique used is descriptive statistics, classic assumption test, multiple regression analysis, coefficient of determination, F-statistical test, and t-statistical test. The data analysis technique used is descriptive statistics, classic assumption test, multiple regression analysis, coefficient of determination, F-statistical test, and t-statistical test. The dependent variable in this study is Transfer Pricing which is Proxied with RTP ( Related Party Transaction) . Independent variables used are Profitability, Tax, Bonus Mechanisms, Foreign Ownership , Debt Covenant and Intangible Assets . The analytical method used in this study is multiple regression analysis with SPSS 20. Based on the results of this study simultaneously Profitability, Taxes, Mechanisms of Bonuses, Foreign Ownership, Debt Covenants and Intangible Assets no significant effect on Transfer Pricing . Partially Only Intangible Assets that affect Transfer Pricing .  The conclusion of this study is that Profitability has no effect on Transfer Pricing, Tax has no effect on Transfer Pricing, Bonus Mechanism has no effect on Transfer Pricing, Foreign Ownership has no effect on Transfer Pricing, Debt Covenant has no effect on Transfer Pricing and Intangible Assets Influence Transfer Pricing. Keywords: Transfer Pricing , profitability, Taxes, Bonus Mechanisms, Foreign Ownership, Debt Covenant , Intangible Assets